1978
DOI: 10.1121/1.381730
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the propagation of very short ultrasonic pulses and their reflection by small targets

Abstract: The field of a circular ultrasonic transducer emitting a single-cycle pulse into water has been observed using a specially constructed small (150 μm) wide-band receiving probe and a compact stroboscopic schlieren system. The theoretically predicted plane-wave and diffracted edge-wave components of the field have been resolved. Good agreement with the theory for a pistonlike source is obtained, except in a region less than 1.5 transducer radii from the transducer. The output of the transducer used in the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 0 publications
2
28
0
3
Order By: Relevance
“…The experimental results were obtained using flat-ended brass cylinders as the targets, the transducer being tilted to achieve the above angles of alignment. A 19mm-diameter heavily-damped lead metaniobate (PMN) transducer was used (Panametrics V3289), earlier work having shown that its behavior was close to that predicted for an ideal-piston radiator [5,8] (as assumed in the present model).…”
Section: Results For Angled Planar Diskssupporting
confidence: 53%
See 1 more Smart Citation
“…The experimental results were obtained using flat-ended brass cylinders as the targets, the transducer being tilted to achieve the above angles of alignment. A 19mm-diameter heavily-damped lead metaniobate (PMN) transducer was used (Panametrics V3289), earlier work having shown that its behavior was close to that predicted for an ideal-piston radiator [5,8] (as assumed in the present model).…”
Section: Results For Angled Planar Diskssupporting
confidence: 53%
“…Considering a point-target of elementary surface se as a rigid point at r T in the fluid, Weight and Hayman [5] have shown it was possible, by reciprocity, to write the reception in the same way as the radiation. The instantaneous pressure at the surface of the receiver <p>(t), defined as, <p>ltl =ffP1r",tl dS, For complex target geometries the principle used to derive the modelling is, starting from Kirchhoff's integral, to widen the reciprocity by making apparent in the integrals a term independent of the reception (i.e.…”
Section: Presentation Of the Model Used In Simulationsmentioning
confidence: 99%
“…The edge wave is generated at the circumference of the transducer, and is due to the relative motion of the transducer and the baffle. The edge wave follows the plane wave in the nearfield and is superimposed in the farfield for a transmitter (Weight and Hayman, 1978), as illustrated in Fig. 9a.…”
Section: It Is Seen Inmentioning
confidence: 99%
“…As explained in [3] the radiation by an ideal plane transducer can be described as the sum of a plane wave coming from the surface of the transducer and a toroldal wave coming from its periphery. On the axis the transient field is formed by two Dirac's pulses of opposite polarity.…”
Section: Tools and Assumptionsmentioning
confidence: 99%
“…Here we displaya geometrical interpretation of the scattering of pulses from broad-band transducers by simple shaped on-axis rigid targets like balls, cones and small disks. This new interpretation is based on two existing theories : the decomposition of the incident field in term of geometrical and edge waves [3], and an adaptation of Dory's "Theorie du Profil Reflecteur" [4]. At first, the underlying theories and approximations used for this interpretation are recalled.…”
mentioning
confidence: 99%